Odpowiedzi

2009-11-25T19:30:34+01:00
3(x+2)²+(2x-1)²-7(x+3)(x-3)=28
3(x²+4x +4) +2x² - 7(x²-9)=28
3x²+12x+12+2x²-7x²+63=28
-2x² + 12x + 63 = 28
-2x² + 12x= 35 /√
-2x + √12x = √35
1 1 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-11-25T19:44:05+01:00
3(x+2)²+(2x-1)²-7(x+3)(x-3) = 28
3(x²+4x+4)+4x²+1-7(x²-9)=28
3x²+12x+12+4x²+1-7x²+63=28
7x²-7x²+12x=28-12-1-63
12x= -48/12
x=-4

x-3 kreska ułamkowa2+x = 4x-1 kreska ułamkowa
2-0,25(2x+3)
Mnożenie na krzyż
(x-3)*2-0,25(2x+3)=(2+x)*(4x-1)
(x-3)* (2-0,5x-0,75)=8x-2+4x²-2
(x-3)*(1,25-0,5x)=4x²+8x-4
1,25x-0,5x²-3,75+1,5x=4x²+8x-4
-4x²-0,5x²-8x+1,25x+1,5x= -4+3,75
-4,5x²-5,25x= -0,25